PERSEPSI IMAM TERHADAP KARYA KATEKESE PAROKI DI KEUSKUPAN SURABAYA - Leonardus Galih Wahyu Pambudi; Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2017)
Catechesis becomes the collective responsibility of all members of the Church. Catechesis become central to the work of the Church's mission in the world, because it involves the faith formation of Church members. Although in general the work of preaching or catechesis is the duty and obligation of all the faithful, but there are some private members who receive ecclesial mandate to be catechists, among others, is a priest. The results of this study showed that 8 of these priests understood with regard to the definition of catechesis and parish catechesis. Although in a different formulation but the essence of catechesis has been understood by the priests. During this time the priests had performed the role of the main responsible in the work of catechesis, but in a different way. The results showed that the concrete manifestation of this role is to teach preparation for reception of the sacrament, giving homilies, and also giving catechesis to the people directly, cooperation and good communication with fellow priests and people of God, it is also the whole pastoral activities, especially catechesis in parishes directed according ARDAS Diocese of Surabaya. Some priests (under 15 years of priesthood) is quite good in formulating a definition of catechesis but still less able to carry out catechesis in parishes optimally, otherwise most of the priest again (above 15 years of priesthood) are less able to formulating the definition and theory but better in implementing catechesis in the parish.